Rare bird documentation form for Bohemian Waxwing at Iowa City, 1984 - Bendorf, Carl J.et al (1984)
Rare bird documentation form for a Bohemian Waxwing at Iowa City in Johnson County, IA on November 11, 1984. Epson - sheet feed